Family Support on the Activities of Elderly Hypertension Patients in Elderly Gymnastics Activities - Wachidah Yuniartika; Fauzan Muhammad (Jurnal Ners, 2019)
Introduction: The aging process results in decreased body resistance, physiological functions and diseases which attack the elderly, such as hypertension. Elderly gymnastics is a mild exercise that is applied to the elderly. High family support will make the elderly more actively participate in elderly gymnastics activities, and vice versa. The aim of study was to determine the relationship of Family Support to the Activity of Elderly in Pajang Village.Methods: The design of the study was quantitative research with a cross sectional approach. The population of the study was all elderly people with hypertension who were aged 60 years and over who participated in elderly gymnastics, with total sampling at 95 respondents. This was then analyzed using the Kendall’s Tau formula.Results: The majority of family support was enough (38.8%) and the active category (63.2%),  with bivariate analysis a value of 0.001 (<0.05), with a magnitude of 0.082.Conclusion: Families can help overcome the problems of the elderly and provide support for exercise activities. Families can also increase self-confidence to improve the health of the elderly. There is a significant relationship of family support for the activeness of elderly hypertension patients in elderly gymnastics activities in Pajang Village.